1999
DOI: 10.1021/cm990193t
|View full text |Cite
|
Sign up to set email alerts
|

Novel Layer-by-layer Complexation Technique and Properties of the Fabricated Films

Abstract: A novel layer-by-layer complex-fabrication technique for multilayer film assembly was developed by alternatively dipping desired substrates in macromolecular ligands and Eu 3+ ion solutions. A water-soluble, luminescent thiophene-based polymer, viz., poly [2,5-(3carboxymethyl urethanyl ethyl) thiophene] (H-PURET), was prepared and used as the macromolecular ligand. Multilayer deposition was monitored using UV-visible spectroscopy by following the absorbance increase due to the deposition of the polymer layer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
47
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 54 publications
(67 reference statements)
0
47
0
Order By: Relevance
“…The question arises of what might be the limit of number charges the molecules should have to ensure layer-by-layer adsorption. In (12)(13)(14) it was shown that the multivalent dyes or ions can be used for multilayer build-up on macroscopic flat surfaces, but these films are not stable in high ionic strengths. In relation to polyelectrolyte capsules the possibility to vary the stability of the capsule wall composed of multilayers opens perspectives to control capsule degradation and release of encapsulated materials.…”
Section: Introductionmentioning
confidence: 99%
“…The question arises of what might be the limit of number charges the molecules should have to ensure layer-by-layer adsorption. In (12)(13)(14) it was shown that the multivalent dyes or ions can be used for multilayer build-up on macroscopic flat surfaces, but these films are not stable in high ionic strengths. In relation to polyelectrolyte capsules the possibility to vary the stability of the capsule wall composed of multilayers opens perspectives to control capsule degradation and release of encapsulated materials.…”
Section: Introductionmentioning
confidence: 99%
“…3 Forces between the layers are primarily electrostatic interaction and covalent bonding, but they can also involve hydrogen bonding, p-p interaction, and coordination bonding of monomeric or polymeric ligands with transition metal ions. 4,5 A relatively weaker charge transfer (CT) interaction as the driving force of the LBL self-assembly was recently used to prepare ultrathin films. [6][7][8][9] Incorporation of noble metal nanoparticles into the LBL films consisting of pconjugated conducting polymers presents promising materials for both catalytic applications, in which conducting polymer beds with catalyst nanoparticles gathering close to the film surfaces provide optimum catalytic situations, and nanotechnological fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…Layer-by-layer assembled films were used as nanoreactors for generation of inorganic nanoparticles [110]. Surface complexation and sequential ligand exchange reactions in transition metal cation complexes also allowed for the growth of thin polymeric films through layer-by-layer stepwise adsorption procedure [111,112]. That approach was used to produce slowly soluble films formed by PSS/Tb 3+ complex in polyelectrolyte nanocapsules [113].…”
Section: Introductionmentioning
confidence: 99%